Nutrient Addition Modifies Phosphatase Activities along an Altitudinal Gradient in a Tropical Montane Forest in Southern Ecuador - Dietrich, Karla; Spoeri, Elena; Oelmann, Yvonne (Frontiers in Earth Science, 2016)
Atmospheric nutrient deposition and climate change are expected to endanger the diversity of tropical forest ecosystems. Nitrogen (N) deposition might influence nutrient fluxes beyond the N cycle by a concomitant increased demand for other nutritional elements such as phosphorus (P). Organisms might respond to the increased P demand by enhanced activity of enzymes involved in releasing inorganic P from organic matter (OM). Our aims were to assess the effect of (i) climate shifts (approximated by an altitudinal gradient), and (ii) nutrient addition (N, P, N+P) on phosphatase activity (PA) in organic layer and mineral soil of a tropical montane rainforest in Southern Ecuador. A nutrient manipulation experiment (NUMEX) was set up along an altitudinal gradient (1000, 2000, and 3000 m a.s.l.). We determined PA and inorganic and total P concentrations. PA at 1000 m was significantly lower (mean ± standard error: 48 ± 20 μmol p-NP g−1 dm h−1) as compared to 2000 and 3000 m (119 ± 11 and 137 ± 19, respectively). One explanation might be that very rapid decomposition of OM at 1000 m results in very thin organic layers reducing the stabilization of enzymes and thus, resulting in leaching loss of enzymes under the humid tropical climate. We found no effect of N addition on PA neither in the organic layer nor in mineral soil, probably because of the low nutrient addition rates that showed ambiguous results so far on productivity measures as a proxy for P demand. In the organic layers of P and N+P treatments, we found decreased PA and increased concentrations of inorganic P. This indicates that the surplus of inorganic P reduced the biosynthesis of phosphatase enzymes. PA in megadiverse montane rainforests is likely to be unaffected by increased atmospheric N deposition but reduced upon atmospheric P deposition.